Language policies- impact on language maintenance and teaching focus on Malaysia Singapore and The Philippines - David, M.K. (2008)
This paper will describe the language policies, planning and implementation in selected ASEAN countries and discuss the impact of such policies on the maintenance of a number of languages and dialects. The paper will specifically examine the minority languages in Malaysia, Singapore and the Philippines that have been and are being abandoned, and examin how language policies, planning and implementation contribute to language shift and language death. Language learning of minority endangered languages can take place in institutional or community settings. In such settings the use of 'multiliteracies' to revive 'threatened' language in new learning venues will be discussed.